Modern Management Paradigms as an Element of the Value Enhancement of Companies in the Food Industry - Firlej, Krzysztof; Bargieł, Aleksandra (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article looks at modern paradigms of management from a theoretical and analytical point of view. It is assumed that these paradigms play a part in improving how companies in the food industry function. The theoretical part presents an evaluation and the current state of management paradigms. These paradigms are than collated in the aspect of their use in the process of managing food industry companies. Individual management paradigms are then tested for how they work in company operations, noting that their correct use has a significant influence on increasing the company’s value and market position. The analysis of operations in this area confirmed that the companies considered here are highly interested in doing what they can to effectively improve their market value, and that they also keep abreast of scientific research as well as their rivals’ behaviour. Employing all of these means, they try to accomplish their goals.